Medium-Term Pulmonary Function Test After Thoracoscopic Lobectomy and Segmentectomy for Congenital Lung Malformation: A Comparative Study With Normal Control - Huang, Jin-Xi; Hong, Song-Ming; Hong, Jun-Jie; Chen, Qiang; Cao, Hua (Frontiers in Pediatrics, 2021)
Purpose: This study aimed to compare the outcomes and pulmonary function test (PFT) of thoracoscopic segmentectomy and lobectomy in infants with congenital lung malformation (CLM), and study the result of PFT on a medium term basis. Methods: The clinical data of 19 infants with CLM who underwent thoracoscopic surgery in our hospital from January 2018 to March 2019 were retrospectively studied, these infants were paired with another 19 infants who underwent thoracoscopic lobectomy during the same period using propensity score matching. Age-matched healthy individuals with similar body size were recruited for PFT as the control group. Patient characteristics, postoperative PFT and outcomes were extracted for statistical analysis.. Results: The average length of hospital stay did not significantly differ between segmentectomy and lobectomy groups. The segmentectomy group had more chest tube drainage than lobectomy group. PFT one month after the operation showed that the tidal volume (VT) of the lobectomy group was lower than that of the segmentectomy group. Time to peak expiratory flow (TPTEF)/time of expiration (TE) and peak flow (PF)/terminal airway velocity (V25%) indicated small airway dysfunction in the lobectomy group, and no obvious abnormalities were found in “time of inspiratory (TI)/TE” in either group. Re-examination of pulmonary function two years after the operation showed that the small airway function of the segmentectomy group returned to normal, and no significant difference in pulmonary function was noted among the three groups. Conclusion: The short-term pulmonary function recovery was better after segmentectomy than after lobectomy. Patients who underwent thoracoscopic lobectomy and segmentectomy have normal lung function two years after the operation.